2004
DOI: 10.1021/jp049714c
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Conformational Flexibility of Methyl α-Cellobioside in Solution by NMR Spectroscopy and Molecular Simulations

Abstract: The conformational flexibility of methyl α-cellobioside in water and dimethyl sulfoxide solutions was investigated by 1D 1H,H T-ROESY experiments. In combination with molecular dynamics simulations, effective proton−proton distances could be derived using experimentally determined cross-relaxation rates. An anti-ψ-conformational state was present in both solvents confirming a previous flexibility hypothesis at this torsion angle. In water solution, an anti-φ-conformational state was also detected and quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…The speed of production of the maps was enhanced by approximately tenfold over that using the full DFT, by the use of a reduced basis set on the carbon atoms in conjunction with the B3LYP functional (B3LYP/4-31G), while maintaining the B3LYP/6-31?G* functional for all other atoms, thus preserving the hydrogen bonding abilities of the higher level DFT calculations. The production of these maps enhances our abilities in making more specific comparisons to experimental results Sivchik and Zhbankov 1977;Andrianov et al 1980; Hamer et al 1978;Horii et al 1982Horii et al , 1983Korolik et al 1985;Tvaroska and Taravel 1992;Duus et al 1994;Sugiyama et al 2000;Suzuki et al 2009;Cheetham et al 2003;Larsson et al 2004;Olsson et al 2008;Cocinero et al 2009;Asensio and Jimenez-Barbero 1995; Chu and Jeffrey 1968) as will be described later. Examination of previous DFT optimization studies on cellobiose (Strati et al 2002a, b;Bosma et al 2006a, b) showed that different rotamers of the hydroxymethyl groups influenced the conformational low energy regions at the glycosidic bonds.…”
Section: Introductionmentioning
confidence: 93%
“…The speed of production of the maps was enhanced by approximately tenfold over that using the full DFT, by the use of a reduced basis set on the carbon atoms in conjunction with the B3LYP functional (B3LYP/4-31G), while maintaining the B3LYP/6-31?G* functional for all other atoms, thus preserving the hydrogen bonding abilities of the higher level DFT calculations. The production of these maps enhances our abilities in making more specific comparisons to experimental results Sivchik and Zhbankov 1977;Andrianov et al 1980; Hamer et al 1978;Horii et al 1982Horii et al , 1983Korolik et al 1985;Tvaroska and Taravel 1992;Duus et al 1994;Sugiyama et al 2000;Suzuki et al 2009;Cheetham et al 2003;Larsson et al 2004;Olsson et al 2008;Cocinero et al 2009;Asensio and Jimenez-Barbero 1995; Chu and Jeffrey 1968) as will be described later. Examination of previous DFT optimization studies on cellobiose (Strati et al 2002a, b;Bosma et al 2006a, b) showed that different rotamers of the hydroxymethyl groups influenced the conformational low energy regions at the glycosidic bonds.…”
Section: Introductionmentioning
confidence: 93%
“…A strong cross peak between the cellobiose 1′ and 4 protons established that the glycosidic linkage was in the syn conformation (32), giving the required flat profile (Fig. 3).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The reasons for these structural preferences are as yet not understood and continue to be a topic of considerable research interest. However, in light of our findings, cellobiose in the condensed state, when placed in a strongly acidic environment (perhaps consisting of a solvent other than water, which competes strongly for the proton), might present a different picture of the ratios of trans versus cis species than expected based on the neutral species abundance ratios, estimated by Larsson in water solution to be 93% trans CB and 7% cis CB conformations, at 300 K. 49 …”
Section: Structure and Energeticsmentioning
confidence: 45%
“…Nevertheless, the enhancement of cis over trans in the isolated cellobiose, by protonation, is of considerable interest in exploring the balance between the two species also in different environs. While it is known experimentally as well as theoretically [40][41][42][43][44][45][46][47][48][49][50] that cis is more stable than trans CB in the isolated species and also in small water clusters [25][26][27] in the gas phase, in neutral condensed phase environs, both crystal and in solution, the energetic balance favours the trans species. The reasons for these structural preferences are as yet not understood and continue to be a topic of considerable research interest.…”
Section: Structure and Energeticsmentioning
confidence: 99%